Data-driven structural damage monitoring and assessment based on unmanned aerial vehicle images: a survey - Zhuoyue Yang; Yuxin Xu; Hao Song; Kang Yu (International Journal of Digital Earth)
The increasing adoption of UAV-based remote sensing has transformed disaster response, structural health monitoring, urban building management, topographic change analysis, and disaster rescue. The collection of image information and the assessment of structural damage based on drones are key technologies for rapidly responding to disasters and providing strategic planning and deployment. Image-based assessment methods face challenges, including difficulty in extracting image features, multiple constraints on data acquisition, and difficulties in integrating evaluation results. This study provides a systematic review of UAV-based structural monitoring and assessment methodologies, categorizing existing techniques based on their data type and applications. This review clarifies the concepts and practical requirements of structural monitoring and assessment processes. Key technologies in data acquisition, map construction and model creation for regular monitoring and rescue assessment were sorted out. The selection of assessment models is closely related to the different types of maps. Finally, future developments in drone image evaluation are discussed and summarized, providing a reference for their application in civilian fields.